2020
DOI: 10.7554/elife.56547
|View full text |Cite
|
Sign up to set email alerts
|

Growth cone-localized microtubule organizing center establishes microtubule orientation in dendrites

Abstract: A polarized arrangement of neuronal microtubule arrays is the foundation of membrane trafficking and subcellular compartmentalization. Conserved among both invertebrates and vertebrates, axons contain exclusively 'plus-end-out' microtubules while dendrites contain a high percentage of 'minus-end-out' microtubules, the origins of which have been a mystery. Here we show that in Caenorhabditis elegans the dendritic growth cone contains a non-centrosomal microtubule organizing center, which generates minus-end-out… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(80 citation statements)
references
References 55 publications
5
75
0
Order By: Relevance
“…As human and mouse WDR62 are known to play prominent roles in neuronal development (Shohayeb et al, 2018), we investigated the localization of WDR-62 in the developing PVD neuron, a highly branched nocioceptor. Intriguingly, we found that WDR-62 localizes to the tip of the outgrowing PVD dendrite (arrowhead, Figure 2F), a site that was recently shown to contain a migrating ncMTOC enriched for microtubules and ɣ-TuRC ( Figure 2F) (Liang et al, 2020). Our discovery of WDR-62 in many polarized cell types provided a unique opportunity to study its role beyond the centrosome.…”
Section: Proximity Interactors Exhibit Localization Patterns Similar mentioning
confidence: 60%
See 2 more Smart Citations
“…As human and mouse WDR62 are known to play prominent roles in neuronal development (Shohayeb et al, 2018), we investigated the localization of WDR-62 in the developing PVD neuron, a highly branched nocioceptor. Intriguingly, we found that WDR-62 localizes to the tip of the outgrowing PVD dendrite (arrowhead, Figure 2F), a site that was recently shown to contain a migrating ncMTOC enriched for microtubules and ɣ-TuRC ( Figure 2F) (Liang et al, 2020). Our discovery of WDR-62 in many polarized cell types provided a unique opportunity to study its role beyond the centrosome.…”
Section: Proximity Interactors Exhibit Localization Patterns Similar mentioning
confidence: 60%
“…The ncMTOC could be a phase-separated structure, as PTRN-1 and several PTRN-1 proximity interactors contain intrinsically disordered regions. Alternatively, and consistent with the colocalization of displaced microtubules with membrane puncta in VAB-10 gut (-) embryos, membranous structures could serve as a platform for ncMTOC assembly as Golgi, Golgi outposts, and endosomes have all been shown to associate with non-centrosomal microtubules (Ori-McKenney et al, 2012;Efimov et al, 2007;Hehnly & Doxsey 2014;Liang et al, 2020). Thus PAR-3 and other polarity regulators could merely position an otherwise autonomous structure.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Our observation that endogenously-tagged γ-tubulin localises to branchpoints supports this conclusion. Moreover, it was recently shown that an endosome-based MTOC tracks the growing dendritic growth cone within C. elegans PVD neurons and nucleates microtubules that travel back towards the soma ( Liang et al, 2020 ). The authors also suggest that a similar process may occur in newly developing Drosophila class I neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, microtubules continue to grow within the soma ( Nguyen et al, 2011 ; Sánchez-Huertas et al, 2016 ), and in mammalian neurons this depends in part on the HAUS complex ( Sánchez-Huertas et al, 2016 ), which is also important for microtubule growth within axons and dendrites ( Cunha-Ferreira et al, 2018 ; Sánchez-Huertas et al, 2016 ). Some MTOCs have been identified within dendrites: the basal body, or its surrounding region, within the distal part of C. elegans ciliated neurons acts as an MTOC, as does a similar region within the URX non-ciliated neuron ( Harterink et al, 2018 ); an MTOC made from endosomes that tracks the dendritic growth cone in C. elegans PVD neurons has recently been identified ( Liang et al, 2020 ); and fragments of Golgi called Golgi outposts within the dendrites of Drosophila dendritic arborisation (da) neurons are thought to recruit γ-TuRCs and act as MTOCs ( Ori-McKenney et al, 2012 ; Yalgin et al, 2015 ; Zhou et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%